TINDAK TUTUR PERLOKUSI DALAM WEBSERIES-NYA RADIT PADA AKUN YOUTUBE RADITYA DIKA TAHUN 2021 (KAJIAN PRAGMATIK) - Mutiara Mahrani; Afif Rofii; Supriyati Supriyati (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to describe perlocutionary speech acts in Webseries Radit, which was broadcast on Raditya Dika's YouTube channel in 2021. This study examines how language functions in digital interactions, focusing on six perlocutionary functions according to Leech (1993): persuading, encouraging, frightening, comforting, deceiving, and entertaining. The research method used was descriptive qualitative with pragmatic analysis. Data were obtained from 17 episodes through listening techniques and recording relevant utterances. The results showed 77 perlocutionary data with a predominance of persuading and encouraging functions, confirming that persuasive strategies are more frequently used in interactions between characters. This finding confirms the role of perlocutionary effects in digital communication and opens up opportunities for further research on web series with different characteristics.